Nurses’ knowledge of the medical triage at the emergency unit of an Iraqi teaching hospital - Hajwal, Salim K.; Al-Taee, Mahdi Hamzah; Ayad, Zahraa M.; Hassan, Abbas Abdul-Hussein; Khaleel, Muna Abdulwahab; Muhaibes, Fakhria Jaber; Abbas, Alaa Hamza; Ridha-Salman, Hayder; H. Abbas, Zahraa (Pharmakeftiki, 2025)
Triage refers to the placement of patients in the appropriate setting at the appropriate time in order for them to receive the appropriate level of care, along with the allocation of resources tailored to their medical needs. A descriptive study was conducted in order to assess nurses’ knowledge of medical triage between October 15, 2023, and April 1, 2024. A non-probability convenience sample comprising 50 nurses working in the Emergency Unit of the Al Hillah Teaching Hospital was included. The study utilized a questionnaire developed through a comprehensive review of the relevant literature and modified as necessary. Its content validity was established through evaluation by a panel of five experts. Data were collected using a researcher-developed, self-administered questionnaire in Arabic, employing both interview and self-report formats. Data analysis was performed using the SPSS software, version 24. The general level of nurses’ knowledge regarding medical triage, as assessed in this study, was found to be fair to good. It is recommended to appoint qualified registered nurses so as to enhance the quality of care provided in medical triage settings.